2016
DOI: 10.1186/s13020-016-0088-7
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture therapy for drug addiction

Abstract: Acupuncture therapy has been used to treat substance abuse. This study aims to review experimental studies examining the effects of acupuncture on addiction. Research and review articles on acupuncture treatment of substance abuse published between January 2000 and September 2014 were searched using the databases ISI Web of Science Core Collection and EBSCO’s MEDLINE Complete. Clinical trial studies on the efficacy of acupuncture therapy for substance abuse were classified according to substance (cocaine, opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…A five-point auricular protocol was developed by the National Acupuncture Detoxification Association in the 1980s, and a body point electrical stimulation protocol was designed by a Chinese doctor in the 1990s [ 7 ]. Researchers have attempted to elucidate the therapeutic effects of acupuncture on reducing addiction-related symptoms and regulating brain dysfunction using various treatment protocols [ 8 , 9 ]. Despite methodological differences in acupuncture points, treatment durations, and types of control conditions among studies [ 9 ], a recent meta-analysis study demonstrated a significant beneficial effect of acupuncture on addiction-related clinical symptoms, such as withdrawal/craving and anxiety, with a medium to large effect size, although the data were heterogeneous and had a significant publication bias [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A five-point auricular protocol was developed by the National Acupuncture Detoxification Association in the 1980s, and a body point electrical stimulation protocol was designed by a Chinese doctor in the 1990s [ 7 ]. Researchers have attempted to elucidate the therapeutic effects of acupuncture on reducing addiction-related symptoms and regulating brain dysfunction using various treatment protocols [ 8 , 9 ]. Despite methodological differences in acupuncture points, treatment durations, and types of control conditions among studies [ 9 ], a recent meta-analysis study demonstrated a significant beneficial effect of acupuncture on addiction-related clinical symptoms, such as withdrawal/craving and anxiety, with a medium to large effect size, although the data were heterogeneous and had a significant publication bias [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, stimulation of PC6 can effectively treat Internet addiction [43] and alleviate the withdrawal syndrome of heroin addiction [44]; the acupoint is also involved in neurotransmitter regulation [45]. It seems compatible with the above description; ST36 has also been reported to influence opioid-induced addiction and side effects; however ST36 was not effective on the current METH study with no reports of the cocaine studies [46]. All the aforementioned findings suggest that acupuncture at specific acupoints, which regulate the dopaminergic pathway in the NAc, can be used for treating specific drug addictions.…”
Section: Discussionmentioning
confidence: 66%
“…In traditional Asian medicine, acupuncture is a popular nonpharmacological treatment option for drug addiction, such as that of alcohol, nicotine, and heroin [11, 46]. Acupuncture research is difficult because the accurate treatment duration, acupuncture frequency, duration of stimulation, acupoint and control selection, and sufficient sample size cannot be determined; thus, the effects of acupuncture therapy for drug addiction are controversial, particularly in clinical applications [7, 46, 57, 58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture has been shown to be effective for reducing drug addiction in preclinical and clinical trials [ 5 ]. In particular, acupuncture has been accepted to be an effective detoxification method for drug addiction as a standard procedure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%